Assessment of Economic Life of Firefighting and Rescue Appliances Based on Chassis Renault Midlum in the Zlin Region - Ladislav Janosik; Ivana Janosikova; Pavel Polednak (Communications - Scientific letters of the University of Zilina, 2016)
This paper is focused on the evaluation of economic data obtained from operational records of fire-fighting equipment with a focus on Firefighting and Rescue Appliance type of vehicles, especially on exit vehicles based on the chassis Renault Midlum, during the period 2006 - 2013. These vehicles were operated by professional units of the Fire and Rescue Service of the Zlin Region. The paper’s aim is to specify the optimum lifetime of the fire-fighting vehicles by the marginal analysis of fire-fighting vehicles’ economical operation. Theoretic calculations of the optimum lifetime have been processed with implementing both the method of exponential trends, and Brown method. The residual value of vehicles has been calculated both according to the current Czech tax law, and to the Expert Standard Valuation of motor vehicles in force in the Czech Republic.